Sex Equity for Rural American Women - Birdie H. Holder (Journal of Research in Rural Education, 1982)
There is clear evidence from vocational education enrollments and employment statistics from rural states which shows traditional values to be highly resistant to change regarding females in non-traditional skill/trade areas. These data dramatically demonstrate the need for special programs that can produce changes in attitudes, beliefs, values and behavior on the part of local rural schools and communities leading to greater female enrollment in non-traditional vocational educational programs. An examination of existing programs indicates none specifically focus on the issues discussed above from a systematic approach to change in rural educational systems. This paper suggests a model for sex equity in vocational education in rural education systems. The model recognizes the uniqueness of rural education systems and builds upon these facets to bring about change. This model incorporates all components of a rural education system to interact in the development of programs that will help remove sex-role stereotyping in rural school systems.